Mandible-first and maxilla-first sequencing in virtual surgical planning for orthognathic surgery: comparison of planned and actual outcomes - Bozok, Ece; Özel, Abdullah; Akkoyun, Emine Fulya; Dolanmaz, Elvan (My University, 2024)
Background: Recent studies have shown that virtual planning for orthognathic surgery is an accurate and repeatable method. It is also a fact that surgical sequence can affect the results in terms of accuracy. Various studies stated that both approaches offer comparable results when properly planned and implemented; however, further clinical studies are still needed. This study aims to evaluate the effect of virtual surgical planning (VSP) on surgical outcomes and whether it is affected by mandible-first or maxilla-first approaches. Methods: This study analyzed data from 45 patients who underwent orthognathic surgery due to dentofacial deformity. Six of these patients underwent single-jaw orthognathic surgery, and 39 underwent bimaxillary orthognathic surgery (Maxilla-first group: 21, mandible-first group: 18). The displacements of specific landmarks were assessed by comparing preoperative and postoperative conventional computed tomographies with VSP data. Results: This study showed a statistically significant relationship between the measurements made with the 2 methods (r =.944; P =.0001). The fact that the intra-class correlation coefficient value is statistically significant and relatively high and that most of the differences in the Bland–Altman chart fall between the limits of compliance indicates a correlation between the virtual plan and surgical outcomes. In addition, in vertical measurements, the absolute mean difference of the B point and the Pogonion in the Maxilla-first group were statistically significantly higher than in the Mandible-first group (P =.038, P =.011). Conclusions: Our findings corroborate the high accuracy of the VSP reported in previous studies and also demonstrate that VSP with both maxilla-first and mandible-first sequencing achieves high accuracy in the sagittal and coronal planes. Although virtual planning significantly influences accurate surgical outcomes, it is not the sole determinant. Factors like condylar positioning and fixation methods can also impact the final results.
Keywords: Mandible-First; Maxilla-First; Orthognathic Surgery; Virtual Surgical Planning